Prevalence of cervicitis agents: literature review - Carvalho, Newton S. (2023)
International and Brazilian literature review was made about the prevalence of cervicitis agents. Clamidia was observed with prevalence between 2,6and 13,9% with 5,6% media rate. The American study evaluated young people between 18 and 26 years old found 13,9% for clamidia prevalence. Gonococos was found with lower prevalence rather than Clamidida. This prevalence was between 0,43 and 19,8% with 5,43% medium, but this isan incorrect value because the high prevalence with 19% was found in Africa in STD clinic increasing the medium value. We have a lack of date in Brazil but for clamidia was found prevalence between 0,6 until 20,2 analyzing 16 Brazilian states. In conclusion we have had finding that this cervicitis agents has high prevalence, and need more studies, mainly in our sites in order to observe the real data.